2012
DOI: 10.1097/hco.0b013e328357428a
|View full text |Cite
|
Sign up to set email alerts
|

Medical therapy for peripheral arterial disease

Abstract: PAD is associated with increased risk of cardiovascular morbidity and mortality. Medical therapy is targeted toward systemic atherosclerosis and risk factor modification. Exercise therapy is the most studied and validated therapy for symptomatic peripheral arterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…Atherosclerotic process is characterized by combination of different morphological, histological and hemorheological changes in the arteries. Contrary to the common belief, atherosclerotic process can begin already at a young age and remain asymptomatic for a long period [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerotic process is characterized by combination of different morphological, histological and hemorheological changes in the arteries. Contrary to the common belief, atherosclerotic process can begin already at a young age and remain asymptomatic for a long period [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of direct anti-atherosclerosis therapy is necessary to induce regression of the existing atherosclerotic lesions and prevent their de novo formation. Despite the large amount of data from basic and clinical studies, no existing drugs were proven effective for the treatment of existing plaques, lowering the volume of lipid necrotic core and stabilizing the fibrous cap simultaneously [1][2][3][4][5][6][7][8][9]. Modern anti-atherosclerotic drugs can be divided into 2 big groups: statins (inhibitors of hydroxymethylglutaryl-coenzyme A reductase) and calcium antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, when evaluating smoking in the sub-population of people with peripheral arterial disease, it was found that approximately 26% smoke, and as many as 79% have a smoking history, either current or former (Dunkley, et al, 2007). Smoking is a top modifiable risk factor contributing to PAD, second only to diabetes (Alexopoulos, Vlachopoulos, & Stefanadis, 2010;Conen et al, 2011;Hennrikus et al, 2010;Federman and Kravetz, 2007;Katsiki, Papadopoulou, Fachantidou, & Mikhailidis, 2013;Lu, Mackay, & Pell, 2014;Moyer, 2013;Muir, 2009;Paraskevas, Papas, Pavlidis, Bessias, & Andrikopoulos, 2008;Simmons, Steffen, & Sanders, 2012;Sontheimer, 2006;Steffen, Duprez, Boucher, Ershow, & Hirch, 2008;Verma, Prasad, Elkadi, & Chi, 2011;Watson, Watson, & Pater, 2006;Wiley, Kumar, & Vacek, 2012). Increased pack years of smoking increases the risks of developing PAD, and increases the morbidity and mortality of the diagnosis, demonstrating a dose-dependent relationship between the two (Au, Golledge, Walker, Haigh, & Nelson, 2013;Hankey, Norman, & Eikelboom, 2006;Katsiki et al, 2013;Lee et al, 2011;Paraskevas et al, 2008;Watson, Watson, & Pater, 2006).…”
Section: Problem Statementsmentioning
confidence: 99%
“…Peripheral arterial disease of the extremities is diagnosed clinically by the ankle brachial index (ABI), a diagnostic tool which is assessed with standard protocols and calculates the index using a ratio of the highest systolic blood pressure in the arm compared with the highest systolic pressure in the legs. Peripheral arterial disease is defined by an ABI of 0.90 or less, and the ABI is associated with high sensitivity and specificity (Aboyans et al, 2011;Aiman et al, 2014;Aronow, 2007a;Aronow, 2007b;Aronow, 2010;Federman and Kravetz, 2007;Hankey et al, 2006;Hennion & Siano, 2013;Hennrikus et al, 2010;Hiatt & Krantz, 2006;Kroger et al, 2009;Lee et al, 2011;Madia, 2012;Moyer, 2013;Simmons, Steffen, & Sanders, 2012;Sontheimer, 2006;Steffen et al, 2008;Verma et al, 2011;Watson, Watson, & Pater, 2006;Wiley, Kumar, & Vacek, 2012). Low ABIs have been proven to be an independent risk factor of cardiovascular risk and as a predictor for future cardiac events such as coronary artery disease, stroke, and death Hankey et al, 2006;Steffen et al, 2008).…”
Section: Peripheral Arterial Disease Smoking and Smoking Cessationmentioning
confidence: 99%
“…Simmons, Steffen, & Sanders, 2012). Intermittent claudication is the mildest symptomatic manifestation of PAD (Lauret et al, 2012).…”
Section: Physical Assessmentmentioning
confidence: 99%